2021
DOI: 10.3390/su13137218
|View full text |Cite
|
Sign up to set email alerts
|

Critical Leaf Water Content for Maize Photosynthesis under Drought Stress and Its Response to Rewatering

Abstract: Crop photosynthesis is closely related to leaf water content (LWC), and clarifying the LWC conditions at critical points in crop photosynthesis has great theoretical and practical value for accurately monitoring drought and providing early drought warnings. This experiment was conducted to study the response of LWC to drought and rewatering and to determine the LWC at which maize photosynthesis reaches a maximum and minimum and thus changes from a state of stomatal limitation (SL) to non-stomatal limitation (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…As long as the leaf remains green, it means that the assimilation process is still going on, i.e., the plant is still alive. And under drought stress, leaves lose water and wilt, chlorophyll content decreases and a series of other physiological changes (Song et al, 2021), which eventually lead to the loss of green and death of the leaves and hinder the normal physiological activities.…”
Section: Discussionmentioning
confidence: 99%
“…As long as the leaf remains green, it means that the assimilation process is still going on, i.e., the plant is still alive. And under drought stress, leaves lose water and wilt, chlorophyll content decreases and a series of other physiological changes (Song et al, 2021), which eventually lead to the loss of green and death of the leaves and hinder the normal physiological activities.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of water stress, the stomata in leaves close during the early stage of drought, which consequently reduces the uptake of CO 2 to below the amount that is required for photosynthesis. This disrupts photosynthesis, and can lead to an imbalance between the photochemical activity of PSII and the electrons required for the Calvin–Benson cycle, which results in the excess absorption of excitation energy and subsequent photoinhibition damage to the PSII reaction centers [ 31 ], and ultimately leads to a decrease in crop photosynthesis [ 32 ]. Numerous studies have shown that severe drought stress can significantly reduce the photosynthetic capacity of crops, which causes a decrease in the chlorophyll content and net saturated photosynthetic rate (Asat), G s , and Fv/Fm [ 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological properties of plant drought tolerance are expressed under both drought stress and the recovery process that follows re-watering. The inhibitory effect of drought on plant growth can be compensated by appropriate water supplementation [ 32 ]. The leaf water potential in maize and cotton has been reported to decrease under water deficit conditions, but it rapidly recovers to equal or higher levels after re-watering, as compared with the control, to compensate for the loss of growth owing to drought [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dry conditions and crop water requirements can be identified by determining tissue water status at the organ and canopy to improve the sustainability of food security and water use in agricultural land (Browne et al, 2020). Identification of dry vegetation and remote sensing monitoring with leaf water content could accurately reflect the level of dry plants and predict plant growth and development capabilities (Song et al, 2021). The estimated soil moisture content in this study provides the information that the leaf water content of vegetation in the Eromoko agricultural land mostly has low water content and impacts low crop production.…”
Section: The Distribution Of Agricultural Land Droughtmentioning
confidence: 99%